(3ebGQHI fXGejIs - (3YjSi(B, (3jMIs ((3GdLRGFQ(B:s (3OGQ GdNdOhfjI(B,s, 2010)
(3hXjaI GdEfJGL(B-(3CfhGY GdEfJGL(B- (3WQjbI GdEfJGL GddMXj(B- (3fXGe GdeLehYGJ GdJcfhdhLjI(B- (3NOeGJ GdJNWjW(B- (3GdHQeLI GdNWjI(B- (3fXGe eJYOO GdbfhGJ(B- (3eQGbHI GdfhYjI(B- (3eMOOGJ GdLhOI(B- (3NQGFW GdeQGbHI Ydi GdefJLGJ GdJj dG jecf bjGSgG(B- (3GdLhOI GdTGedI(B.s
(3GTcGd U(B.123s
Keywords: (3EOGQI GdEfJGLs; (3GdHQeLjGJs; (3GdJNRjfs; (3JcfhdhLjG(B- (3GfJGLs